2007
DOI: 10.1111/j.1471-4159.2007.04604.x
|View full text |Cite
|
Sign up to set email alerts
|

The lipophilic metal chelators DP‐109 and DP‐460 are neuroprotective in a transgenic mouse model of amyotrophic lateral sclerosis

Abstract: One of the hypotheses for the development of familial amyotrophic lateral sclerosis (ALS) is that mutations in the superoxide dismutase 1 enzyme lead to aberrant properties of the copper within the active site of the enzyme which then causes increased oxidative damage. The lipophilic metal chelators DP-109 and DP-460 which chelate calcium, copper, and zinc were tested in the G93A-transgenic ALS mouse model. Both compounds significantly extended survival, DP-109 (5 mg/kg/day) by 10%, DP-460 (10 mg/kg/day) by 9%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 56 publications
(52 reference statements)
0
33
0
1
Order By: Relevance
“…To further test the effect of metal concentration, we supplemented the food with metal chelators, notably DP-109 and DP-460 of the family of 'membrane-activated chelators' (MACs). By attaching to the cell membrane, MACs avoid the problems that could be caused by a general chelation of metals, and they were shown to reduce amyloid pathology in Tg2576 mice (Lee et al, 2004;Kolusheva et al, 2005; see also Petri et al, 2007). Indeed we found that DP-109, a zinc/copper chelator, increased the fraction of Ab42-expressing flies developing to adulthood ( Figure 4A).…”
Section: Figure 1 Expression Of Ab42 In Drosophilamentioning
confidence: 63%
“…To further test the effect of metal concentration, we supplemented the food with metal chelators, notably DP-109 and DP-460 of the family of 'membrane-activated chelators' (MACs). By attaching to the cell membrane, MACs avoid the problems that could be caused by a general chelation of metals, and they were shown to reduce amyloid pathology in Tg2576 mice (Lee et al, 2004;Kolusheva et al, 2005; see also Petri et al, 2007). Indeed we found that DP-109, a zinc/copper chelator, increased the fraction of Ab42-expressing flies developing to adulthood ( Figure 4A).…”
Section: Figure 1 Expression Of Ab42 In Drosophilamentioning
confidence: 63%
“…Although application of recombinant TNF-binding protein-1 (rhTBP-1) had protective effects in wobbler mice -another model of motor neuron degeneration -the treatment did not in fact reduce TNFα levels in the CNS [27]. The beneficial effects of treatments as diverse as thalidomide, folic acid, insulin-like growth factor-1, and metal chelators are all correlated in SOD1 mice with reductions in TNFα levels [28][29][30][31]. However, it does not seem likely that they all act through TNFα/TNFR directly to prevent degeneration; the reductions more probably reflect a decrease in inflammation secondary to neuroprotection by other mechanisms.…”
Section: Involvement Of Death Receptors In Disease Mechanism and Thermentioning
confidence: 99%
“…There is increased oxidative damage in cases of both sporadic and familial ALS, and also in animal models of ALS (Carrí et al, 2003). Although no alteration in total copper was observed in mutant SOD1 transgenic mice (Subramaniam et al, 2002), copper, zinc, and calcium chelators have been shown to be protective (Hottinger et al, 1997;Nagano et al, 2003;Petri et al, 2007). However, there are reports of iron accumulation in the CNS of both familial and sporadic forms of ALS (Oba et al, 1993;Imon et al, 1995;Kasarskis et al, 1995).…”
Section: Introductionmentioning
confidence: 99%